2019
DOI: 10.1111/ans.15492
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use prior to elective surgery is strongly associated with persistent use following surgery: an analysis of 14 354 Medicare patients

Abstract: BackgroundPersistent opioid use following total joint replacement (TJR) surgery is common; however, the association between pre‐surgical opioid use and surgery type has not been established. The objective of this study was to determine the association between pre‐surgery opioid use and persistent post‐surgery opioid use in TJR patients compared to other elective surgical patients.MethodsThis is a retrospective cohort study, of univariate and multinomial logistic regression of linked, de‐identified Medicare Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Not surprisingly, preoperative opioid use is associated with longer durations of postoperative opioid prescribing, more refills after surgery, and increased postoperative daily oral morphine equivalent consumption. 25,26 It is also a clear risk factor for chronic postoperative opioid use. 10,[27][28][29][30][31] Between 64 and 77% of chronic opioid users before surgery continue to fill opioids postoperatively.…”
Section: Persistent Postoperative Opioid Use Is More Common In Preope...mentioning
confidence: 99%
“…Not surprisingly, preoperative opioid use is associated with longer durations of postoperative opioid prescribing, more refills after surgery, and increased postoperative daily oral morphine equivalent consumption. 25,26 It is also a clear risk factor for chronic postoperative opioid use. 10,[27][28][29][30][31] Between 64 and 77% of chronic opioid users before surgery continue to fill opioids postoperatively.…”
Section: Persistent Postoperative Opioid Use Is More Common In Preope...mentioning
confidence: 99%
“…The use of Medicare rebate data has recently been validated for use in assessing epidemiological trends, 39 and to identify significant unexplained variation in surgical management of breast cancer between states 40 . Similar to other studies using comparable methodology, our understanding is that rebate data is representative of privately insured patients who had operations in public or private hospitals 40–44 . Interestingly, some studies report that these data are all inclusive of both public and privately insured patients 45,46 .…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have found that persistent opioid use after surgery was more common in patients who used opioids preoperatively and that patients using opioids preoperatively had lower functional scores postoperatively (Catchpool et al, 2019;Pivec et al, 2014). One study showed that a majority of Medicare beneficiaries received opioids within the year leading up to TJA (Jin et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%